New bis‐ferrocenyl end‐capped peptides: synthesis and charge transfer properties1. Issue 1 (19th January 2013) - Donoli, Alessandro; Marcuzzo, Vanessa; Moretto, Alessandro; Crisma, Marco; Toniolo, Claudio; Cardena, Roberta; Bisello, Annalisa; Santi, Saverio; Maran, Flavio; Toniolo, Claudio
Abstract In this article, the successful preparation of a new series of 310‐helical peptides of different length containing two terminal ferrocenyl (Fc) units and based on the strongly foldameric α‐aminoisobutyric (Aib) acid is reported. The synthesis of the FcCO(Aib)nNHFc (n = 1−5) homo‐peptides was performed by solution methods. Moderate to good yields (26−85%) were obtained in each of the difficult coupling steps of FcCOOH and the corresponding H(Aib)nNHFc compounds by C‐activation with the 1‐(3‐dimethylaminopropyl)‐3‐ethylcarbodiimide/7‐aza‐1‐hydroxy‐1, 2, 3‐benzotriazole method. Information on the CO···HN intramolecularly hydrogen‐bonded networks was initially obtained from FT‐IR absorption measurements. The NH stretching (amide A) region allowed us to distinguish which amide protons are involved in intramolecular hydrogen bonds and indicates the formation of an incipient 310‐helix structure for peptides containing at least two Aib residues. This conclusion was confirmed by 1H NMR titrations of the NH groups of the peptides in CDCl3 with dimethylsulfoxide and by crystallographic analysis of the Nα‐acylated FcCO(Aib)5NHFc pentapeptide amide. The two redox‐active Fc groups covalently bound to the termini of the foldameric peptide architectures were used as electrochemical probes. The end‐to‐end effects of electron holes generated by single and double oxidations were analyzed by means of electrochemical and spectroelectrochemical techniques. The results of these studies indicate that charge transfer across the peptide main chain does occur in the five peptides. In particular, in the pentapeptide 5, charge is transferred through an intramolecular Fe···Fe separation of 14 Å. © 2012 Wiley Periodicals, Inc. Biopolymers (Pept Sci) 100: 71–81, 2013.